Diverse Cone-Snail Species Harbor Closely Related Streptomyces Species with Conserved Chemical and Genetic Profiles, Including Polycyclic Tetramic Acid Macrolactams - Quezada, Michelle; Licona-Cassani, Cuauhtemoc; Cruz-Morales, Pablo; Salim, Angela A.; Marcellin, Esteban; Capon, Robert J.; Barona-Gómez, Francisco (Frontiers in Microbiology, 2017)
Streptomyces are Gram-positive bacteria that occupy diverse ecological niches including host-associations with animals and plants. Members of this genus are known for their overwhelming repertoire of natural products, which has been exploited for almost a century as a source of medicines and agrochemicals. Notwithstanding intense scientific and commercial interest in Streptomyces natural products, surprisingly little is known of the intra- and/or inter-species ecological roles played by these metabolites. In this report we describe the chemical structures, biological properties, and biosynthetic relationships between natural products produced by Streptomyces isolated from internal tissues of predatory Conus snails, collected from the Great Barrier Reef, Australia. Using chromatographic, spectroscopic and bioassays methodology, we demonstrate that Streptomyces isolated from five different Conus species produce identical chemical and antifungal profiles – comprising a suite of polycyclic tetramic acid macrolactams (PTMs). To investigate possible ecological (and evolutionary) relationships we used genome analyses to reveal a close taxonomic relationship with other sponge-derived and free-living PTM producing Streptomyces (i.e. Streptomyces albus). In-depth phylogenomic analysis of PTM biosynthetic gene clusters (BGCs) indicated PTM structure diversity was governed by a small repertoire of genetic elements, including discrete gene acquisition events involving dehydrogenases. Overall, our study shows a Streptomyces-Conus ecological relationship that is concomitant with specific PTM chemical profiles. We provide an evolutionary framework to explain this relationship, driven by anti-fungal properties that protect Conus snails from fungal pathogens.